2013
DOI: 10.14748/ssm.v45i2.319
|View full text |Cite
|
Sign up to set email alerts
|

Sambucus ebulus - from traditional medicine to recent studies

Abstract: Sambucus ebulus L. (SE) (Dwarf elder) is an herbaceous plant well-known in traditional medicine of Balkans and Anatolia for its healing effects in many disorders. It has been used for a long time for treatment of inflammation-related gastrointestinal disorders, influenza, kidney and lung diseases, and rheumatoid arthritis as well as of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In traditional Iranian medicine, it is used topically to treat in ammations caused by insect bites and also some herbs such as nettle [15,16]. It has been revealed that leaf extract of SE had an inhibitory effect on in ammatory cytokines IL-1 (IL-1α & IL-1 ) and TNF-α [17]. Moreover, other studies revealed that SE contains several compounds, including phenolic acids, avonoids, steroid, vitamin C, caffeic acid, anthocyanins and cyanogen lycosides [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Iranian medicine, it is used topically to treat in ammations caused by insect bites and also some herbs such as nettle [15,16]. It has been revealed that leaf extract of SE had an inhibitory effect on in ammatory cytokines IL-1 (IL-1α & IL-1 ) and TNF-α [17]. Moreover, other studies revealed that SE contains several compounds, including phenolic acids, avonoids, steroid, vitamin C, caffeic acid, anthocyanins and cyanogen lycosides [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenol preparations and polyphenol-rich extracts have also the potential to improve lipid profile [174][175][176][177]. As it was already mentioned, S. ebulus fruits are a rich source of polyphenols and especially of anthocyanins [33,108]. Also, it was found that the aqueous and aqueous alcoholic extracts of agrimony have a high polyphenol content [25,178], although their exact polyphenol composition has not yet been identified.…”
Section: Plants That Affect Lipid Metabolismmentioning
confidence: 99%
“…It is known as 'Palemʼ or 'Aghtii' in Iran and distributed in Northern coast of Caspian Sea like Mazandaran province (6). Flavonoids, phenols, steroids, tannins, sambunigrin, glycosides, cardiac glycosides, caffeic acid derivatives, chlorogenic acid, ursolic acid, ebulitins, ebulin and volatile substances of these species were previously reported (6)(7)(8). In traditional medicine, extracts of different parts of the herb like leaves, rhizome, root and fruitsused in treating some inflammatory cases such as, bee and nettle bites, arthritis and sore-throat, burns and infectious wounds, edema, eczema, urticaria, hemorrhoids, rheumatism (6,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids, phenols, steroids, tannins, sambunigrin, glycosides, cardiac glycosides, caffeic acid derivatives, chlorogenic acid, ursolic acid, ebulitins, ebulin and volatile substances of these species were previously reported (6)(7)(8). In traditional medicine, extracts of different parts of the herb like leaves, rhizome, root and fruitsused in treating some inflammatory cases such as, bee and nettle bites, arthritis and sore-throat, burns and infectious wounds, edema, eczema, urticaria, hemorrhoids, rheumatism (6,7,9). In other studies some effects of S. ebulus were investigated Anti-inflammatory and antinociceptive (10), antioxidant (11,12) anticancer (13) and antibacterial (14) effects.…”
Section: Introductionmentioning
confidence: 99%